Synchronization of Switched Complex Bipartite Neural Networks with Infinite Distributed Delays and Derivative Coupling - Qiuxiang Bian; Jinde Cao; Jie Wu; Hongxing Yao; Tingfang Zhang; Xiaoxu Ling (Abstract and Applied Analysis)
A new model of switched complex bipartite neural network (SCBNN) with infinite distributed delays and derivative coupling is established. Using linear matrix inequality (LMI) approach, some synchronization criteria are proposed to ensure the synchronization between two SCBNNs by constructing effective controllers. Some numerical simulations are provided to illustrate the effectiveness of the theoretical results obtained in this paper.